Perspectivas para el control del Virus de la Diarrea Viral Bovina (BVDV) - Vargas, Diana S.; Jaime, Jairo; Vera, Víctor J. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary Bovine Viral Diarrhea Virus (BVDV) is one of the most important infectious agents in cattle population. BVDV is widespread throughout the world and it is endemic disease in most of the cattle population where 40 to 80% are seropositive. It causes economic losses mainly in breeding cattle. BVDV genetic and antigenic diversity is due to the virus high mutation and recombination frequency, which is reflected in many clinical manifestations and the difficult control of the disease. Control and prevention measures implemented by some countries are based on the elimination of the main source of infection: the persistently infected animals (PI animals), as well as the improvement of the immune response through the use of vaccines. Immunization with inactivated and modified-live vaccines has been used for decades without any significant improvement. New experimental strategies are being developed: recombinant vaccines where BVDV specific genes are selected in order to immunize cattle and thus overcome the shortcomings of conventional vaccines.